PENINGKATAN KINERJA UKM DENGAN MENGIMPLEMENTASIKAN INFORMASI AKUNTANSI MANAJEMEN YANG DIDUKUNG OLEH INFORMASI ANTAR UNIT - Siti Alliyah; Riskin Hidayat (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2014)
This research aims to test the effect of the use of management accounting system (MAS) to the Small and Medium Enterprises (SMEs) management performance moderating with interdepence unit. This research use survey method with sampel is Small and Medium Enterprises (SMEs) in Kabupaten Rembang, with cluster sampling obtained sample 186 SMEs. Analysis of the data using linear regression moderating. Result of research refer that management accounting system (MAS) have an influence on positive to SMEs management performance. This suggest that SAM an influence to performance management (SMEs) stronger when moderated by interdependence.